Allometric relationship in the bioaccumulation of radionuclides (134Cs & 241Am) and delineation of contamination pathways (food and seawater) in bloody cockle Anadara senilis using radiotracer techniques. (December 2018) - Kuranchie-Mensah, Harriet; Pouil, Simon; Teyssié, Jean-Louis; Oberhänsli, François; Warnau, Michel; Metian, Marc
Abstract: The uptake and depuration kinetics of 134 Cs and 241 Am were investigated in the bloody cockle Anadara senilis exposed via seawater and food in controlled conditions, using animals of different weight groups in order to assess how their bioaccumulation is affected by allometry and, hence, the individual's age. This study is one of the few experiments investigating bioaccumulation capacities of radionuclides in a West-African bivalve. Results showed that allometric relationships were mainly dependent on the exposure pathway considered. Significant relationships with body weight of bloody cockles were found during the uptake from dissolved phase for both radionuclides; they followed inverse power functions: smaller cockles concentrated both radionuclides more than larger ones. In contrast, radionuclide absorption and assimilation efficiencies from water and food, respectively, did not show any significant relationship with weight: only slight variation was observed between small and large organisms for the retention of 241 Am accumulated from food. A bioaccumulation model was used to assess the contribution of each pathway of exposure (food vs. water) in organisms grouped in small and large individuals. We found that, regardless of the size, 134 Cs was mainly bioaccumulated through the dietary pathway. In the case of 241 Am, the relative contribution of each pathway is weight-dependent: major contribution of dissolved pathway in smaller organisms and the major dietary contribution in larger organisms. Highlights: This study assessed the radionuclide accumulation capacities of the bloody cockle. Relationship of body weight to 134 Cs and 241 Am accumulation capacities were tested. Bivalve weight influenced bioaccumulation capacities for dissolved 134 Cs and 241 Am. Sampling strategy for Cs and Am biomonitoring program needs to consider the weight.